2007
DOI: 10.1093/cercor/bhm127
|View full text |Cite
|
Sign up to set email alerts
|

Visual, Somatosensory, and Bimodal Activities in the Macaque Parietal Area PEc

Abstract: Caudal area PE (PEc) of the macaque posterior parietal cortex has been shown to be a crucial node in visuomotor coordination during reaching. The present study was aimed at studying visual and somatosensory organization of this cortical area. Visual stimulations activated 53% of PEc neurons. The overwhelming majority (89%) of these visual cells were best activated by a dark stimulus on a lighter background. Somatosensory stimulations activated 56% of PEc neurons: most were joint neurons (73%); a minority (24%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
62
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 42 publications
11
62
0
Order By: Relevance
“…In this study, we found that the posterior parts of the parietal leg and toe areas overlap or adjoin retinotopic areas activated by looming stimuli predominantly in the lower visual field. We suggest that they could be human homologs of a multisensory area in the caudal part of the superior parietal lobule (area PEc) of macaque monkeys (21,22), and that they are important for visually guided locomotion. One limitation of the present study is that looming stimuli were presented near the face but not close to the lower body.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In this study, we found that the posterior parts of the parietal leg and toe areas overlap or adjoin retinotopic areas activated by looming stimuli predominantly in the lower visual field. We suggest that they could be human homologs of a multisensory area in the caudal part of the superior parietal lobule (area PEc) of macaque monkeys (21,22), and that they are important for visually guided locomotion. One limitation of the present study is that looming stimuli were presented near the face but not close to the lower body.…”
Section: Discussionmentioning
confidence: 91%
“…Hindlimb representations in the medial PPC have been suggested by recent studies on nonhuman primates (15,18,21,22). In this study, we found parietal leg and toe areas at the superior and medial end of the postcentral sulcus, a superior parietal region that is posterior to S-I in the postcentral gyrus driven by passive stimulation on the foot (49, 50), anterior to a posterior parietal area activated by self-generated foot movements with visual feedback (51), and consistent with a superior parietal area activated during the planning of foot movements (25).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Bimodal responses in single V6A cells were assessed by testing a cell with both somatosensory and visual stimulations. To avoid biases, the two types of stimulation were performed across cells in a randomized order (Breveglieri et al, 2008).…”
Section: Somatosensory Stimulationmentioning
confidence: 99%
“…For example, neurons in caudal Brodmann area 5 (PEc) (Pandya and Seltzer, 1982) located in the posterior part of the superior parietal lobule show a strong contralateral-limb bias after somatosensory stimulation to the limbs (Breveglieri et al, 2006). A subgroup of these PEc neurons respond to both visual and somatosensory stimuli (Breveglieri et al, 2008). Many neurons in MIP that respond to somatosensory stimulation also show a contralateral-limb bias in visually guided reaching (Colby and Duhamel, 1991).…”
Section: Potential Roles Of the Activity On Ipsilateral-limb Trialsmentioning
confidence: 99%